Experimental Investigation on the Drying of Loosely-Packed and Heterogeneous Municipal Solid Waste - Nzioka, A. M.; Kim, M. G.; Hwang, H. U.; Yan, C. Z.; Ved, V. E.; Meshalkin, V. P.; Kim, Y. J. (Pleiades Publishing, 2016)
In this paper, experimental investigation on convective drying of mixed municipal solid wastes was conducted. The aim of this study was to determine the effect of temperature, change in composition and particle size on the overall drying rate coefficient and mass transfer coefficient. Particle size of the samples was determined and mass losses recorded with time when the samples were dried using convective dryer. Mass losses were used to determine moisture content, drying rate coefficient and mass transfer coefficient. Experimental results showing the effect of temperature, changes in the composition of organic waste and particle size were presented.
Keywords: municipal solid waste; convective drying; drying rate coefficient; particle size; composition